First molecular data of the Borneo Banteng Bos Javanicus lowi from Sabah, Borneo - Hisashi Matsubayashi; Kei Hanzawa; Tomohiro Kono; Taichiro Ishige; Takashi Gakuhari; Peter Lagan; Indra Sunjoto; Jum Rafiah Abdul Sukor; Waidi Sinun; Abdul Hamid Ahmad (De Gruyter, 2014)
Phylogenetic relationships among three subspecies of banteng, Burma banteng Bos javanicus birmanicus in mainland Southeast Asia, Javan banteng Bos javanicus javanicus in Java, and Bornean banteng Bos javanicus lowi in Borneo, and the presence/absence of interbreeding between wild Bornean banteng and domestic cattle in Sabah, Malaysia, were investigated by partial sequences of cytochrome b and D-loop of mitochondrial DNA. The results show that genetic distance of the Bornean banteng are relatively close to the gaur Bos gaurus/gayal Bos frontalis (the cytochrome b, 0.004–0.025; the D-loop, 0.012–0.021) followed by Burma banteng (the cytochrome b, 0.027–0.035; the D-loop, 0.040–0.045), and kouprey Bos sauveli (the cytochrome b, 0.031–0.035; the D-loop, 0.037–0.042). There are much greater distances between Bornean banteng and domestic cattle, Bos taurus and Bos indicus (the cytochrome b, 0.059–0.076; the D-loop, 0.081–0.090). These results suggest that the Bornean banteng diverged genetically from other banteng subspecies and that the wild Bornean banteng from this study are pure strain and have high conservation value.